Thermosetting maleimide resin composition

The thermosetting maleimide resin composition, formulated with specific components and modifications, addresses the issues of separation and compatibility in existing compositions, achieving excellent dielectric properties and adhesion for high-frequency substrate applications.

JP7660990B2Active Publication Date: 2025-04-14SHIN ETSU CHEMICAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021183052
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-10
Publication Date
2025-04-14
Estimated Expiration
2041-11-10

AI Technical Summary

Technical Problem

Existing thermosetting maleimide resin compositions are varnish-like, prone to separation, and lack compatibility, resulting in unsuitable dielectric properties and adhesion for high-frequency applications such as 5G substrates.

Method used

A thermosetting maleimide resin composition comprising styrene-based elastomers with reactive functional groups, a maleimide compound, epoxy resins, and an anionic polymerization initiation catalyst, with specific ratios and modifications to ensure compatibility and stability.

Benefits of technology

The composition achieves excellent dielectric properties and strong adhesion to organic resins and metals, preventing separation and turbidity, making it suitable for high-frequency substrate applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660990000001
    Figure 0007660990000001
  • Figure 0007660990000002
    Figure 0007660990000002
  • Figure 0007660990000003
    Figure 0007660990000003
Patent Text Reader

Abstract

To provide a heat-curable maleimide resin composition that does not exhibit turbidity or separation in the form of a varnish, and yields a cured product that has excellent dielectric properties and has a strong adhesive force even to organic resins such as LCP and MPI and copper.SOLUTION: A heat-curable maleimide resin composition contains: (A) a styrene-based elastomer having a reactive functional group at both ends; (B) a maleimide compound represented by the following formula (1) (where R1 represents a dimer acid skeleton-derived divalent hydrocarbon group); (C) an epoxy resin having at least two epoxy groups per molecule; and (D) an anionic polymerization initiating catalyst, wherein a ratio between the components (A) and (B) (mass ratio (A) / (B)) is 2 to 20.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermosetting maleimide resin composition, an uncured or cured resin film made of the resin composition, an adhesive, a sealing material, and a substrate containing a cured product of the thermosetting maleimide resin composition. [Background technology]

[0002] In recent years, the next-generation mobile communication system known as 5G has become popular, aiming to realize high-speed, large-capacity, low-latency communications. To realize this, materials for high-frequency bands are required, and since reducing transmission loss is essential as a noise countermeasure, there is a demand for the development of insulating materials with excellent dielectric properties (low dielectric constant and low dielectric tangent).

[0003] Among these, insulating materials with excellent dielectric properties are in demand for circuit board applications. Insulating materials with excellent dielectric properties are required for circuit boards such as rigid and flexible circuit boards, and reactive polyphenylene ether resins (PPE) are being used for rigid circuit boards, while liquid crystal polymers (LCPs) and modified polyimides (MPIs) with improved properties are being used for flexible printed circuit boards (FPCs).

[0004] When manufacturing the above FPC, an adhesive is required to attach the base film and coverlay film to the surface having the wiring portion by using a heat press, etc. Traditionally, adhesives that mainly use epoxy resins have been used, but recently there has been a demand for adhesives with excellent dielectric properties.

[0005] In light of this background, adhesives with excellent dielectric properties have been reported (for example, Patent Documents 1 to 4), but most of them are combinations of epoxy resins, other thermosetting resins, and thermoplastic resins. These compositions have excellent dielectric properties in the frequency range of 10 GHz or less, but 5G requires them to have dielectric properties in the frequency range of 28 GHz or more, known as millimeter waves, and many of the adhesives that were previously said to have excellent dielectric properties do not currently have sufficient dielectric properties.

[0006] In addition, a resin composition containing a special maleimide compound and a thermoplastic resin has been disclosed as a composition that has excellent high-frequency characteristics and also has a high level of adhesion to conductors (Patent Document 5). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2008-248141 A [Patent Document 2] JP 2011-68713 A [Patent Document 3] International Publication No. 2016-17473 [Patent Document 4] JP 2016-79354 A [Patent Document 5] International Publication No. 2018-16489 Summary of the Invention [Problem to be solved by the invention]

[0008] However, the resin composition described in Patent Document 5 is in a varnish state, and the resins are not compatible with each other, so that separation of the varnish occurs, and it has been confirmed that a resin film cannot be obtained, or even if a resin film is obtained, it does not exhibit adhesiveness, and it has been found to be unsuitable for substrate applications. Accordingly, an object of the present invention is to provide a thermosetting maleimide resin composition which is in a varnish form and which gives a cured product which is free from turbidity and separation, has excellent dielectric properties, and has strong adhesive strength even to organic resins such as LCP and MPI, and to copper, as well as to provide an uncured or cured resin film, an adhesive, and a substrate made thereof, and a substrate containing a cured product of the thermosetting maleimide resin composition. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems and have found that the following thermosetting maleimide resin composition can achieve the above object, thereby completing the present invention.

[0010] <1> (A) a styrene-based elastomer having reactive functional groups at both ends, (B) a maleimide compound represented by the following formula (1): [ka] (In formula (1), R 1 represents a divalent hydrocarbon group derived from a dimer acid skeleton. (C) Epoxy resin having two or more epoxy groups in one molecule and (D) Anionic polymerization initiator catalyst wherein the ratio of component (A) to component (B) (mass ratio (A) / (B)) is 2 to 20. <2> The styrene-based elastomer of component (A) is a copolymer of styrene with an alkene and / or a non-conjugated diene, and the reactive functional groups at both ends of the copolymer contain at least one of an amino group, a carboxyl group, and a vinyl group. <1> 2. The thermosetting maleimide resin composition according to claim 1 . <3> The component (D) is at least one compound selected from the group consisting of imidazole compounds, phosphorus compounds, and amine compounds. <1> or <2> 2. The thermosetting maleimide resin composition according to claim 1 . <4> <1> ~ <3> 2. An uncured resin film comprising the thermosetting maleimide resin composition according to claim 1. <5> <1> ~ <3> 2. A cured resin film comprising a cured product of the thermosetting maleimide resin composition according to claim 1. <6> <1> ~ <3> 2. An adhesive comprising the thermosetting maleimide resin composition according to claim 1. <7> <1> ~ <3> 2. An encapsulating material comprising the thermosetting maleimide resin composition according to claim 1. <8> <1> ~ <3> 2. A substrate comprising a cured product of the thermosetting maleimide resin composition according to claim 1. Effect of the Invention

[0011] The thermosetting maleimide resin composition of the present invention does not separate or become turbid even when made into a varnish, and the cured product thereof has excellent dielectric properties and adhesive strength, and has particularly strong adhesive strength to organic resins such as LCP and MPI, as well as to copper. Therefore, the thermosetting maleimide resin composition of the present invention is particularly useful as a material for FPCs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will now be described in more detail.

[0013] (A) Styrene-based elastomer having reactive functional groups at both ends The styrene-based elastomer of component (A) mainly contributes to improving the dielectric properties, heat resistance, and adhesiveness of the cured product of the composition at high frequencies, as well as improving the flexibility of the composition when made into a film, and is not particularly limited as long as it is a thermoplastic elastomer having a structural unit derived from a styrene-based compound and having reactive functional groups at both ends, and may be a thermoplastic elastomer having a structural unit derived from styrene.

[0014] In the present invention, the styrene-based elastomer is preferably a copolymer of styrene and an alkene and / or a non-conjugated diene, which is partially or completely hydrogenated. That is, it is a block copolymer and / or a random copolymer with styrene as a hard segment and alkene and / or a non-conjugated diene as a soft segment. Examples of the styrene-based elastomer include styrene / butadiene / styrene block / random copolymer, styrene / isoprene / styrene block / random copolymer, styrene / ethylene / butylene / styrene block / random copolymer, styrene / ethylene / propylene / styrene block / random copolymer, and styrene / butadiene block / random copolymer. Block copolymers are preferred from the viewpoint of quality stability.

[0015] From the viewpoint of heat resistance, it is preferable to use styrene / ethylene / butylene / styrene block / random copolymer, styrene / ethylene / propylene / styrene block / random copolymer, styrene / butadiene block / random copolymer, etc., in which the double bonds of the conjugated diene component have been eliminated by a hydrogenation reaction (hydrogenation). The hydrogenation may be partial or complete, but complete hydrogenation or one with a high hydrogenation rate is more preferable from the viewpoint of heat resistance.

[0016] The mass ratio of styrene / conjugated diene and its double bond hydrogenated portion in the styrene copolymer is preferably 10 / 90 to 70 / 30, more preferably 20 / 80 to 67 / 33. If the mass ratio is within this range, a composition with excellent compatibility and dispersibility and stable quality can be obtained. That is, the styrene content by mass in the styrene-based elastomer is preferably 10 to 90%, more preferably 20 to 67%.

[0017] In addition, both ends of the styrene-based elastomer of the component (A) are modified with at least one reactive functional group selected from the group consisting of amino, carboxyl, and vinyl groups. As a result, the component (A) reacts with the component (B) described below to obtain a cured product with excellent heat resistance. The modification of the styrene-based elastomer can be carried out, for example, by copolymerizing an unsaturated carboxylic acid during polymerization of the styrene-based elastomer. It can also be carried out by heating and kneading the styrene-based elastomer and the unsaturated carboxylic acid in the presence of an organic peroxide. Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid, itaconic acid, fumaric acid, maleic anhydride, itaconic anhydride, and fumaric anhydride. The method of amine-modifying the styrene-based elastomer is not particularly limited, and known methods can be used. For example, it can be carried out by copolymerizing an unsaturated monomer containing an amino group with the styrene-based elastomer. It can also be carried out by polymerization using a polymerization initiator containing an amino group.

[0018] The number average molecular weight (Mn) of component (A) is preferably 10,000 to 300,000, and more preferably 10,000 to 200,000. When the number average molecular weight is within the above range, the resulting composition has excellent film properties, excellent compatibility and dispersibility with other components such as components (B) and (C), and exhibits good adhesion. The number average molecular weight referred to in this specification refers to the number average molecular weight measured by gel permeation chromatography (GPC) under the following conditions using polystyrene as a standard substance.

[0019] [Measurement conditions] Developing solvent: Tetrahydrofuran (THF) Flow rate: 0.35mL / min Detector: Refractive index detector (RI) Column: TSK Guardcolumn SuperH-L TSKgel SuperHZ4000(4.6mmI.D.×15cm×1) TSKgel SuperHZ3000(4.6mmI.D.×15cm×1) TSKgel SuperHZ2000 (4.6mmI.D.×15cm×2) (All manufactured by Tosoh Corporation) Column temperature: 40℃ Sample injection volume: 5 μL (0.2% by mass in THF solution)

[0020] The styrene-based elastomer (A) may be a commercially available product. Specific examples include the Tuftec series manufactured by Asahi Kasei Corporation and the FG series manufactured by Kraton. The composition of the present invention may contain one type of styrene-based elastomer alone or a mixture of two or more types. In the thermosetting maleimide resin composition of the present invention, the blending amount of the component (A) is preferably from 60 to 99 mass %, more preferably from 65 to 95 mass %, and further preferably from 70 to 93 mass %.

[0021] (B) Maleimide Compound The component (B) used in the present invention is a maleimide compound represented by the following formula (1), and is preferably a maleimide compound which is a reaction product of dimer diamine and maleic anhydride. The component (B) is a thermosetting resin, and since it reacts with the component (A), it has good heat resistance and mechanical properties, resulting in a highly reliable composition. In addition, the component (B) has good dielectric properties because it has a divalent hydrocarbon group derived from the dimer acid skeleton. Therefore, the composition exhibits excellent dielectric properties. [ka] (In formula (1), R 1 represents a divalent hydrocarbon group derived from a dimer acid skeleton.

[0022] Dimer acids are liquid fatty acids that are mainly composed of dicarboxylic acids with 36 carbon atoms, produced by dimerization of unsaturated fatty acids with 18 carbon atoms, which are derived from natural products such as vegetable oils. Dimer acids do not have a single skeleton, but rather have multiple structures and exist in several types of isomers. Representative dimer acids are classified as linear (a), monocyclic (b), aromatic (c), and polycyclic (d). In this specification, the dimer acid skeleton refers to a group derived from a dimer diamine having a structure in which the carboxy group of such a dimer acid is substituted with a primary aminomethyl group. Examples of the divalent hydrocarbon group derived from the dimer acid skeleton include, but are not limited to, the following structures. Furthermore, from the viewpoint of the heat resistance and reliability of the cured product, it is more preferable that the divalent hydrocarbon group derived from the dimer acid skeleton of component (B) has a structure in which the carbon-carbon double bond in the hydrocarbon group derived from the dimer acid skeleton is reduced by a hydrogenation reaction. [ka]

[0023] When a maleimide compound other than that represented by formula (1) is used as component (B), its compatibility with component (A) decreases, causing turbidity and separation when made into a varnish, which may lead to unevenness in the composition and variations in the properties of the composition.

[0024] The mass ratio ((A) / (B)) of the component (A) to the component (B) is 2 to 20, and preferably 3 to 15. If this ratio is more than 20, the amount of liquid component increases, which may result in a decrease in film properties. Conversely, if it is less than 2, the amount of thermosetting component decreases, which may result in a decrease in heat resistance.

[0025] (C) Epoxy resin having two or more epoxy groups in one molecule The component (C) used in the present invention is an epoxy resin having two or more epoxy groups in one molecule. The epoxy resin improves the flowability and mechanical properties of the thermosetting maleimide resin composition of the present invention, and improves the adhesive strength to organic resins such as LCP and MPI. Any epoxy resin having two or more epoxy groups in one molecule can be used without particular limitation, but from the viewpoint of compatibility with the components (A) and (B), it is preferable that the epoxy resin is liquid at room temperature (25°C).

[0026] Specific examples of epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, biphenol type epoxy resins such as 3,3',5,5'-tetramethyl-4,4'-biphenol type epoxy resins and 4,4'-biphenol type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A novolac type epoxy resins, naphthalene diol type epoxy resins, trisphenylol methane type epoxy resins, tetrakisphenylol ethane type epoxy resins, phenol biphenyl type epoxy resins, dicyclopentadiene type epoxy resins, biphenyl aralkyl type epoxy resins, epoxy resins obtained by hydrogenating the aromatic rings of phenol dicyclopentadiene novolac type epoxy resins, triazine derivative epoxy resins, and alicyclic epoxy resins. Among these, bisphenol A type epoxy resins are preferably used.

[0027] The amount of component (C) is preferably 0.05 to 10 parts by mass, more preferably 0.1 to 7.0 parts by mass, based on 100 parts by mass of the total amount of components (A) and (B). If the amount is more than this range, the dielectric properties may deteriorate. Conversely, if the amount of component (C) is less than this range, the composition may have poor adhesive strength. Furthermore, the curability may decrease.

[0028] (D) Anionic polymerization initiator catalyst The anionic polymerization initiator catalyst, component (D), is added primarily to initiate and promote the anionic polymerization reaction between components (A), (B) and (C). There are no particular limitations on the component (D) as long as it accelerates the anionic polymerization reaction, and it is preferably at least one compound selected from the group consisting of imidazole compounds, phosphorus compounds, and amine compounds. Specific examples of the imidazole compound include imidazole, 2-methylimidazole, 2-ethylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-undecylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and imidazoles having a diaminotriazine ring such as 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine. Specific examples of phosphorus compounds include tributylphosphine, tri(p-methylphenyl)phosphine, tri(nonylphenyl)phosphine, triphenylphosphine, triphenylphosphine·triphenylborane, and tetraphenylphosphine·tetraphenylborate. Specific examples of the amine compound include triethylamine, benzyldimethylamine, α-methylbenzyldimethylamine, 1,8-diazabicyclo[5.4.0]undecene, and tris(dimethylaminomethyl)phenol. Anionic polymerization initiator catalysts such as imidazole compounds and tertiary amine compounds that open the epoxy groups in component (C) and then form adducts with the epoxy resin that promote the crosslinking reaction of the maleimide compound are particularly preferred.

[0029] The amount of component (D) is preferably 0.01 to 5.0 parts by mass, and more preferably 0.05 to 3.0 parts by mass, per 100 parts by mass of the total amount of components (A) and (B). If it is more than this range, the dielectric properties may deteriorate. On the other hand, if it is less than this range, the curing speed may decrease, which is not preferable.

[0030] <Other additives> The thermosetting maleimide resin composition of the present invention may further contain various additives as necessary within a range that does not impair the effects of the present invention. Examples of such additives include inorganic fillers such as silica, alumina, and boron nitride, resin powders such as PTFE powder, metal particles such as silver, organopolysiloxanes having reactive functional groups, non-functional silicone oils, thermoplastic resins, thermoplastic elastomers other than styrene-based, organic synthetic rubbers, photosensitizers, light stabilizers, polymerization inhibitors, flame retardants, pigments, dyes, etc. In order to improve the electrical properties of the cured product of the thermosetting maleimide resin composition, other additives such as ion trapping agents may be added.

[0031] The thermosetting maleimide resin composition of the present invention can be produced by mixing the components (A), (B), (C), and (D), and, if necessary, other additives. The thermosetting maleimide resin composition of the present invention can also be dissolved in an organic solvent and treated as a varnish. The thermosetting maleimide resin composition can be easily molded into a sheet or film by forming it into a varnish. Any organic solvent can be used without limitation as long as it dissolves the (A) component and the (B) component. As the organic solvent, for example, toluene, xylene, anisole, cyclohexanone, cyclopentanone, etc. can be suitably used. The above organic solvents may be used alone or in combination of two or more kinds. The concentration of the thermosetting maleimide resin composition of the present invention in the varnish is preferably 5 to 80% by mass, more preferably 10 to 75% by mass.

[0032] This thermosetting maleimide resin composition can be suitably used mainly as an adhesive, a primer, a bonding film or sheet material for a substrate, a sealing material, an adhesive layer for a coverlay film for an FPC, or a flexible flat cable. There are no limitations on the method or form of use. For example, it can be used as an uncured resin film or a cured resin film, or as an adhesive. Examples of use are shown below, but are not limited thereto.

[0033] For example, a thermosetting maleimide resin composition (varnish) dissolved in an organic solvent is applied to a support sheet, and then the organic solvent is removed by heating for 0.5 to 5 hours at a temperature of usually 80°C or higher, preferably 100°C or higher, to obtain an uncured film- or sheet-shaped composition. The support sheet may be one that is generally used, such as polyolefin resins such as polyethylene (PE) resin, polypropylene (PP) resin, and polystyrene (PS) resin, and polyester resins such as polyethylene terephthalate (PET) resin, polybutylene terephthalate (PBT) resin, and polycarbonate (PC) resin, and the surface of these support sheets may be subjected to a release treatment. The coating method is not particularly limited, and examples include a gap coater, a curtain coater, a roll coater, and a laminator. The thickness of the coating layer is not particularly limited, and the thickness after distillation of the solvent is in the range of 1 to 100 μm, preferably 3 to 80 μm. Furthermore, a cover film may be used on the coating layer.

[0034] Moreover, a copper foil can be attached onto the coating layer to use it as a substrate material.

[0035] Furthermore, the varnish is applied to the substrate, and the organic solvent is removed by heating for 0.5 to 5 hours at a temperature of usually 80° C. or higher, preferably 100° C. or higher, and the material to be bonded to the substrate is pressure-bonded while being heated, and then heated for 0.5 to 10 hours at a temperature of 130° C. or higher, preferably 150° C. or higher, to achieve adhesion. Examples of the application method include, but are not limited to, a spin coater, a slit coater, a spray, a dip coater, a bar coater, and the like. EXAMPLES

[0036] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0037] (A) Both Styrene-based elastomer with reactive functional groups at the ends (A-1) Amine-modified styrene / ethylene / butylene / styrene block copolymer, hydrogenated, styrene content 30%, number average molecular weight 33,000 (Tuftec MP10: Asahi Kasei Corporation) (A-2) Carboxylic acid modified styrene / ethylene / butylene / styrene block copolymer, styrene content 30%, number average molecular weight 90,000 (Tuftec M1913: Asahi Kasei Corporation) (A-3) Styrene / ethylene / butylene / styrene block copolymer, styrene content 30%, number average molecular weight 74,000 (Tuftec H1041: Asahi Kasei Corporation, for comparison)

[0038] (B) Maleimide Compound (B-1): A bismaleimide compound represented by the following formula (SLK-6895, manufactured by Shin-Etsu Chemical Co., Ltd.) [ka] -C 36 H 70 - represents a hydrocarbon group derived from a dimer acid skeleton. (B-2): A bismaleimide compound represented by the following formula (SLK-3000, manufactured by Shin-Etsu Chemical Co., Ltd., for comparative purposes) [ka] -C 36 H 70 - represents a hydrocarbon group derived from a dimer acid skeleton. (B-3): 4,4'-diphenylmethane bismaleimide (BMI-1000: manufactured by Daiwa Chemical Industry Co., Ltd., for comparison)

[0039] (C) Epoxy resin (C-1): Bisphenol A type epoxy resin (jER-828: manufactured by Mitsubishi Chemical Corporation) (C-2): Biphenyl aralkyl type epoxy resin (NC-3000: manufactured by Nippon Kayaku Co., Ltd.)

[0040] (D) Anionic polymerization initiator catalyst (D-1): 2-ethyl-4-methylimidazole (2E4MZ: manufactured by Shikoku Kasei Co., Ltd.) (D-2): 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine (2MZ-A: manufactured by Shikoku Kasei Co., Ltd.)

[0041] <Preparation of varnish> The components according to the formulations in Tables 1 and 2 were placed in a 500 mL four-neck flask equipped with a Dimroth condenser and a stirrer, and stirred at 50° C. for 2 hours to obtain a varnish-like resin composition.

[0042] <Appearance of varnish> Regarding the varnish before being made into a film, if there was no residual dissolution or turbidity when visually observed, and a 30 mass % xylene solution of the resin composition was placed in a quartz cell, the direct light transmittance at 740 nm with an optical path length of 1 mm was measured at 25°C using a spectrophotometer U-4100 (manufactured by Hitachi High-Tech Science Corp.), those that were 70% or more were marked with ◎, those that were 50% or more but less than 70% were marked with ○, and those that were less than 50% were marked with ×.

[0043] <Preparation of uncured film> The varnish-like thermosetting maleimide resin composition was applied to a PET film having a thickness of 38 μm using a roller coater so that the thickness after drying would be 50 μm, and then dried at 120° C. for 10 minutes to obtain an uncured resin film.

[0044] <Handling of uncured resin film> The uncured resin film was visually inspected for cracks or breakage when it was bent 90 degrees at 25° C. When no cracks, breaks, tackiness, or the like were observed, it was marked with an ◯, and when even a small amount of cracks, breaks, tackiness, or the like was observed, it was marked with an ×.

[0045] [Table 1]

[0046] [Table 2]

[0047] From the results in Tables 1 and 2, it was confirmed that the varnish compositions of Examples 1 to 7 were stable without separation or turbidity. The stability of the varnish compositions was also confirmed in Comparative Examples 3 to 5. On the other hand, the varnishes of Comparative Examples 1 and 2 became turbid.

[0048] From the results in Tables 1 and 2, it was confirmed that there were no cracks or breaks in the uncured resin film properties for Examples 1 to 7. Similarly to the Examples, no cracks or the like were confirmed in Comparative Examples 1, 3, and 5. On the other hand, cracks and tack were observed in Comparative Examples 2 and 4. Further evaluation of Comparative Examples 2 and 4 was discontinued.

[0049] <Dielectric constant, dielectric loss tangent> The uncured resin film was cured at 180° C. for 2 hours, and the resulting resin film was cut to prepare a 60 mm×60 mm test piece. The dielectric constant and dielectric loss tangent of the obtained test piece at 10 GHz and 25° C. were measured using an SPDR dielectric resonator (MS46122B, manufactured by Anritsu Corporation).

[0050] <Heat resistance> The cured resin film produced by the above process was stored at 150°C for 500 hours, and then the dielectric properties were measured at 10 GHz at 25°C using the above device. When the rate of change between the initial dielectric tangent at 10 GHz and the dielectric tangent at 10 GHz after storage was less than 100%, it was evaluated as ◯, and when it was 100% or more, it was evaluated as ×.

[0051] <Peel strength> A slide glass having a length of 75 mm, a width of 25 mm, and a thickness of 1.0 mm was prepared, and the resin composition side of the uncured resin film with a PET film, on which the PET substrate was not attached, was placed on one surface, and lamination was performed under conditions of 120 ° C, 0.3 MPa pressure, and 60 seconds. After lamination, the PET substrate was peeled off, and a 18 μm thick copper foil (Mitsui Kinzoku Co., Ltd., Ra 0.6 μm), a 50 μm thick LCP (Chiyoda Integre Co., Ltd.) or MPI (PIXEO SR, Kaneka Co., Ltd.) was placed on the resin composition surface, and lamination was performed under conditions of 120 ° C, 0.3 MPa pressure, and 60 seconds. After lamination, the adhesive test piece was prepared by curing at 180 ° C for 2 hours.

[0052] To evaluate the adhesion, the 90° peel adhesion strength (kN / m) was measured when peeling the copper foil, LCP, or MPI of each adhesive test piece from the slide glass at a temperature of 23°C and a tensile speed of 50 mm / min in accordance with JIS-C-6481 "Test methods for copper-clad laminates for printed wiring boards."

[0053] The above evaluation results are shown in Tables 3 and 4.

[0054] [Table 3]

[0055] [Table 4]

[0056] From the above results, it has been confirmed that the thermosetting maleimide resin composition of the present invention is free from separation or turbidity of the varnish, has excellent dielectric properties after curing, and exhibits high adhesive strength to metals and organic resins, and is therefore useful as an insulating material suitable for substrate applications.

Claims

1. (A) a styrene-based elastomer having at least one reactive functional group selected from an amino group, a carboxyl group, and a vinyl group at both ends, the styrene-based elastomer being selected from a styrene / ethylene / butylene / styrene block or random copolymer, a styrene / ethylene / propylene / styrene block or random copolymer, and a styrene / butadiene block or random copolymer; (B) a maleimide compound represented by the following formula (1): 【Chemistry 1】 (In formula (1), R 1 represents a divalent hydrocarbon group derived from a dimer acid skeleton.) (C) Epoxy resin having two or more epoxy groups in one molecule and (D) Anionic polymerization initiator catalyst wherein the ratio of component (A) to component (B) (mass ratio (A) / (B)) is 2 to 20.

2. 2. The thermosetting maleimide resin composition according to claim 1, wherein the component (D) is at least one compound selected from the group consisting of imidazole compounds, phosphorus-based compounds and amine compounds.

3. An uncured resin film comprising the thermosetting maleimide resin composition according to claim 1 or 2.

4. A cured resin film comprising a cured product of the thermosetting maleimide resin composition according to claim 1 or 2.

5. An adhesive comprising the thermosetting maleimide resin composition according to claim 1 or 2.

6. An encapsulant comprising the thermosetting maleimide resin composition according to claim 1 or 2.

7. A substrate comprising a cured product of the thermosetting maleimide resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Thermosetting resin composition containing maleimide and / or vinyl compound

    JP1998505599A

  • Flame retardant curable resin composition

    JP2008248141A

  • Coverlay film

    JP2011068713A

  • Resin composition, insulation film and semiconductor device using the same

    JP2016079354A

  • Resin composition

    JP2022036841A